KAJIAN KEBIJAKAN PENDIDIKAN DI MALUKU - Sefanya Sairiltiata; Tanwey Gerson Ratumanan; Theresia Laurens (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to analyze the implementation of education policies in the Maluku region, which has an archipelagic geographical character, with challenges related to access, resource distribution, and disparities in education quality. The qualitative approach used with a case study design allows researchers to deeply understand the dynamics of education policies in a real-world context. Data collection techniques included documentation studies, field observations, and in-depth interviews with education stakeholders. The results indicate that the implementation of education policies in Maluku still faces various obstacles, particularly in infrastructure, education digitalization, and the equitable distribution of teaching staff. National policies tend not to be fully adaptive to the geographical and sociocultural conditions of the archipelagic region. On the other hand, there is positive potential in the development of local content curricula and learning innovations based on local wisdom that can increase the relevance of education for students. The analysis also reveals an imbalance between structural and contextual aspects of policy implementation. Therefore, more adaptive, data-driven, and contextual policies are needed through strengthening synergies between the central and regional governments. Furthermore, the development of locally based education models and the enhancement of human resource capacity are key to achieving equity and improving the quality of education in the Maluku archipelago.